Marketing Strategy Analysis using AHP-SWOT Method to Increase Sales Volume - Minto Waluyo; Gigih Tawang Alam (The Indonesian Journal of Computer Science, 2024)
PT. X is a food manufacturer located in Gresik. Currently, the company, which was established in 2018, is facing an issue, namely a decline in sales figures leading to a significant decrease in profit. Therefore, this research will analyze the existing marketing strategies to propose new strategies to increase sales. The method used in this study is AHP-SWOT. AHP is used to determine the weighting of each aspect, while SWOT is used to determine proposed strategies. Based on the research conducted, it was found that the aspect with the highest weight, at 43.35% as determined by AHP, is the product aspect, which includes product quality, variety, and display. Based on the SWOT results, it was found that PT. X is in quadrant 2, indicating that the company still has strengths but faces various threats. Proposed strategies include increasing product quality with halal-labeled products and expanding promotion reach by utilizing social media campaigns and marketplace.